Performance Evaluation of Combining with Medical and Old-Age Care in Pension Institutions of China: A Two-Stage Data Envelopment Analysis [Corrigendum] - Du N; Wu P; Yuan M; Li Z (Risk Management and Healthcare Policy)
Du N, Wu P, Yuan M, Li Z. Risk Manag Healthc Policy. 2021;14:4211–4222. The authors have advised that the funding statement on page 4221 is incorrect. The text “Grant No. 61703322” should read “Grants No. 52075303 and 61703322”. The authors also wish to add the following reference to the end of the reference section on page 4221. 22. Kao C. Efficiency decomposition for general multi-stage systems in data envelopment analysis. European Journal of Operational Research. 2014;232(1):117-124. The new reference should have been cited in the paper in the following place. Page 4213, left column, first line, the text should read “different sizes and is widely used in efficiency research”.22 The authors apologize for these errors.